Economic crisis and party responsiveness on the left–right dimension in the European Union - Clements, Ben; Nanou, Kyriaki; Real-Dato, José (SAGE, 2018)
The economic crisis within the European Union has had a significant impact on domestic politics in the member states, affecting the links between parties and citizens and accentuating the tensions parties face between governing responsibility and being responsive to public opinion. This article examines whether parties in EU countries have shifted their left–right ideological positions during the current crisis and whether such shifts are a direct response to the pressures of wider economic conditions or are more affected by changes in the preferences of the median voter. Party-based and citizen-based data are examined between 2002 and 2015, encompassing both the precrisis and crisis periods. The main findings are that the economic crisis has made parties less responsive to public opinion on the left–right dimension, and this effect is more pronounced for parties that have been in government.